Rancang Bangun Sistem Monitoring dan Evaluasi Perkuliahan Berbasis Hybrid Programming UNIBI - Sardjono Sardjono; Dzurrahman Roki Muhammad Ibrahim (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2021)
To support Teaching and Learning Activities (KBM),  for a university to have innovations that can fulfill information services that must be delivered to students, lecturers and other units who interest in viewing, monitoring, and evaluating of lecturing activities, that matter accordance with the UNIBI mission to providing the best service for the academic community. To achieve this goal, the innovation is to improve the Academic Information System application (eureka.unibi.ac.id) in providing services that can be accessed by various platforms. By the design of a hybrid programming-based for system monitoring and evaluation lecturing, accordingly the SIAKAD application (eureka.unibi.ac.id) can be implemented into an application that can be accessed by various platforms such as smartphones with Android, iOS or Windows mobile operating systems. By a hybrid-based design, communication between units can occur quickly, and information from the results of monitoring and evaluation of lecturing activities can be directly disseminated and accessed by many division. Tools that use to  development process model used is the Rational Unified Process (RUP).  The RUP provides a well defined structure for the software life cycle. RUP has four phases that can be carried out iteratively which are implemented using the Ionic framework. The result of this research is a guide for developing web-based applications (eureka.unibi.ac.id) to be hybrid-based, where this hybrid-based design is the basis for implementation as an improvement in academic services. Keywords: Siakad, Monitoring, Evaluating, RUP, Lecturing activities, Framework ionic, Hybrid programming